Effects of climate, soil, forest structure and land use on the functional composition of the understorey in Italian forests. (26th September 2019) - Chelli, Stefano; Simonetti, Enrico; Wellstein, Camilla; Campetella, Giandiego; Carnicelli, Stefano; Andreetta, Anna; Giorgini, Daniele; Puletti, Nicola; Bartha, Sandor; Canullo, Roberto
Abstract: Question: In functional biogeography studies, generalizable patterns in the relationship between plant traits and the environment have yet to emerge. Local drivers (i.e., soil, land use, vegetation structure) can increase our understanding of the trait–environment relationship. What is the role of climate and local drivers in shaping abundance‐weighted trait patterns of forest understories at biogeographic scales? Location: Italian forests. Methods: We selected 201 sites that are statistically representative for the heterogeneity of Italian forests across three biogeographic regions (alpine, continental, and mediterranean). Understorey vegetation was recorded for each site on an area of 400 m 2, together with 25 environmental variables related to climate, soil, land use and forest structure. Specific leaf area (SLA), plant height ( H ) and seed mass (SM) were obtained from databases. Community‐weighted mean (CWM) values were calculated. Variance partitioning was used to identify the relative role of groups of environmental variables on the CWM of traits. Generalized Additive Models were used to assess the relationship between traits and single variables. Results: Climate alone and climate–soil interactions explained the largest proportion of the variation of all the traits (13.7% to 22.8%). Temperature‐related factors as well as soil N and P availability were the climatic and edaphic explanatory variables most correlated to trait variation. Forest structure and land use accounted for a smaller percentage of the variation in traits. Land‐use factors alone were important in explaining only SLA variation. Conclusions: While climate plays a major role in trait–environment relationships in forest understories, our results highlighted the need to integrate at least soil properties as local drivers of trait variation in broad scale functional biogeography studies of these systems. Abstract : Climate and climate–soil interactions play a major role in trait–environment relationships in Italian forest understories. Temperature‐related factors as well as soil N and P availability were the climatic and edaphic explanatory variables most correlated to trait variation. Forest structure and land use accounted for a smaller percentage of the variation in traits.